Undergraduate students’ perception of the Indian dental curriculum: A focus-group based, multi-centric questionnaire survey - Rhythm Bains; Vaishnavi Parikh; Pragya Pandey (Journal of Oral Biology and Craniofacial Research)
Aim: the present study was designed to take a student's perception regarding the current dental education curriculum. Methodology: A structured, pre-validated questionnaire made on Google Forms was shared amongst participants pursuing undergraduate dental program in a DCI recognized dental college via e-mail, Facebook or WhatsApp. The questionnaire consisted of questions about the admission procedure (5questions), curriculum design (12 questions) teaching methods (5 questions) and assessment (5 questions) methods. The respondents were divided into 2 focus groups; Pre-clinical: BDS first & second year students and Clinical: BDS third & fourth year students. Results: The questionnaire was circulated amongst a total of 510 potential candidates, out of which 403 responded (response rate 79%). 48.4% (195/403) were from government dental colleges and 51.6% (206/403) were from private dental colleges. Preclinical group had 89 students (1st year = 27, 2nd year = 62) and clinical group 344 students (3rd year = 138, 4th year = 176). Students of both focus groups responded similarly to many questions relating to curriculum (need of syllabus revision, p = 0.912; horizontal/vertical integration, p = 0.076; and early clinical exposure p = 0.843), teaching methods (need of mixed teaching methods) and assessment methods (methods which are not based on quota-chasing p = 0.588). Statistically significant difference was seen to “whether the students are able to retain or relate to the basic sciences subjects taught in first & second year” (p < 0.0001) Conclusion: Students expressed a need for a horizontal & vertical integration of topics, frequent syllabus revision, Early Clinical Exposure, a mixed teaching method, and better assessment methods.